2018
DOI: 10.1177/1938640018776065
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study Comparing Platelet-Rich Plasma Injection With Saline for the Treatment of Plantar Fasciitis Using a Prospective, Randomized Trial Design

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…21,24,29,32 However, recent studies have reported conflicting results when PRP injections were compared with steroid injection and other treatment methods, and in some instances they were unable to demonstrate superiority of the PRP treatment. [17][18][19]27,39,40,47,50 The purpose of this study was to perform a meta-analysis comparing injection of PRP with corticosteroid injections.…”
mentioning
confidence: 99%
“…21,24,29,32 However, recent studies have reported conflicting results when PRP injections were compared with steroid injection and other treatment methods, and in some instances they were unable to demonstrate superiority of the PRP treatment. [17][18][19]27,39,40,47,50 The purpose of this study was to perform a meta-analysis comparing injection of PRP with corticosteroid injections.…”
mentioning
confidence: 99%
“…Two studies comparing PRP and placebo were included in this meta-analysis [ 42 , 43 ]. One article was judged to have an ambiguous bias risk; the other was found to be at a lower risk (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Jain et al [ 37 ] and Sherpy et al [ 39 ] performed trials of different time in the patient, but the participants were not allowed to remain blind. Another experiment conducted by Johnson-Lynn et al [ 42 ] performed a double-blind design, but its selective reporting and allocation of uncertainty concealment reduced the quality of the method. Because blind methods were not applied, the other trials were considered high risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…Across studies, there were a total of 1160 participants, 31% females and 69% males. All studies included patients with various LE musculoskeletal pathologies: Achilles rupture (2), 21,32 Achilles tendinopathy (5), 22,25,26,31,33 lateral ankle sprain (1), 20 high ankle sprain (1), 34 hamstring injury (4), 28,29,36,37 knee osteoarthritis (2), 19,27 acute muscle injury (2), 23,38 patellar tendinopathy (1), 39 and plantar fasciitis (3) 24,30,35 (Table 2). Of the 21 studies, 14 assessed pain 19,20,[22][23][24]27,[30][31][32][33]35,[37][38][39] (VAS, NPRS, KOOS, and EQ-5D), 13 assessed disability [19][20][21][22][24][25][26][27][31][32][33]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Three studies 24,30,35 included 157 participants, with 58% females. The average RoB score was 9.7 (range 9-10).…”
Section: Plantar Fasciitismentioning
confidence: 99%